The role of the traineeship mentor in the undergraduate education of the support teacher - Mirca Montanari; Giorgia Ruzzante (Firenze University Press, 2021)
This contribution, of theoretical nature, proposes some ideas about the practical traineeship of the support teacher, as situational learning, included in a path of university specialization that aims to expand knowledge and cultural and professional skills, in an inclusive perspective, promoting generative learning through the opportunity of a fertile experience born from the virtuous interweaving between university and school. In this context, it becomes essential the competent role of the traineeship mentor in the initial training of the support teacher, inevitably influenced by the unexpected and dramatic historical event of the Covid-19 pandemic, the cause of complex problems and current socio-educational emergencies.   Il ruolo del tutor di tirocinio nella formazione universitaria del docente specializzato Il presente contributo, di carattere teorico, propone alcuni spunti di riflessione in ordine al tirocinio del docente di sostegno, come apprendimento in situazione, inserito in un percorso di specializzazione universitaria che mira ad espandere conoscenze e competenze culturali e professionali, in prospettiva inclusiva, promuovendo l'apprendimento generativo tramite l'opportunità di una fertile esperienza nata dall'intreccio virtuoso tra università e scuola. In tale contesto, diventa imprescindibile il competente ruolo del tutor di tirocinio nella formazione iniziale dell'insegnante specializzato, inevitabilmente influenzata dell'imprevisto e drammatico evento storico mondiale della pandemia da Covid-19 causa scatenante di complesse problematiche e emergenze socio-educative attuali.